Pollen and nectar sources used by honeybee colonies pollinating sunflower (Helianthus annuus) in the Colorado River Valley, Argentina - Andrada, Ana C. (2004)
Pollen traps and beeswax foundations were set in order to study pollen and nectar sources used by honeybee colonies pollinating sunflower (Helianthus annuus L.) for the production of hybrid seed in the lower valley of the Colorado river in southern Argentina. Thirty-seven plant species in bloom were registered in the area surrounding the sunflower field. Most of them were scarcely represented. The honeybee maximum density recorded on the sunflower male-fertile line was 10.00 bees per 100 heads, while on the male-sterile line was 25.33 bees per 100 heads. Seven plant taxa were identified in the pollen loads and 26 in the honey samples. About 84% of the collected pollen came from three taxa: Centaurea solstitialis L., Eucalyptus camaldulensis Dehnh. and Cirsium vulgare (Savi) Airy -Shaw, and only 11% came from H. annuus. The taxa most gathered had high protein values, above 20%. The dominant and secondary pollen types in honey samples were Tamarix gallica L., E. camaldulensis, Brassicaceae and C. solstitialis. The results indicate that honeybees (Apis mellifera L.) foraged pollen and nectar mainly from the flora surrounding the sunflower field.